NI-03 USEFULNESS OF IMP-SPECT IN PREOPERATIVE GRADE EVALUATION OF INTRAORBITAL TUMOR. (16th December 2019) - Okonogi, Shinichi; Kubota, Shuuhei; Sakaeyama, Yuuki; Ueda, Keita; Nemoto, Masaaki; Nagao, Tateki; Sugo, Nobuo
Abstract: INTRODUCTION: The frequency of intraorbital tumors is small as 0.9% of all brain tumors, but its pathological type is diverse. Among them, the diagnosis of whether particularly malignant tumor scan clinically, is extremely important. Nuclear medical testing is essential for non-invasive differential diagnosis in brain tumors. SPECT, good malignancy differentiation, evaluation of malignancy, usefulness such as differentiation of non-tumorous lesions have been reported many. However, there are few reports that SPECT was useful in preoperative differential diagnosis of orbital tumors. Since 123IMP-SPECT was useful in preoperative differential diagnosis of intraorbital tumors, we report some literature considerations. METHOD: Among the 27 cases of intraorbital tumors that were operated on in our clinic between August 2005 and August 2016, 14 cases of SPECT prior to surgery were examined for the usefulness of preoperative differential diagnosis. Breakdown of cases, as the malignant tumor, two cases of malignant lymphoma, MALT lymphoma 2 cases, adenoid cystic carcinoma 1 case, in one case plasma cytoma, as a benign tumor, false tumors 4 cases, three hemangioma cases, neurocytoma 1 case it was. RESULTS: In IMP early image, accumulation of clear IMP was observed in all six cases of malignant tumors. In benign tumors, there is no accumulation in hemangioma and neurosheath, there is a strong accumulation in one of the four cases in false tumors, it was observed mild accumulation in the remaining two cases. Tumor to normal ratio of IMP early image was an average of 2.39 in six malignant tumors and 1.52 in 8 benign tumors. CONCLUSION: This time, we examined the usefulness of 123IMP-SPECT in preoperative differential diagnosis of intraorbital tumors. The T/N ratio of intraorbital malignant tumors is higher than benign tumors, and it was thought to help to evaluate preoperative malignancy of intraorbital tumors.